Report of the Connecticut Labor Bureau - Cummings, Edward (Quarterly Journal of Economics, 1893)
Journal Article Report of the Connecticut Labor Bureau Get access Edward Cummings Edward Cummings Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 7, Issue 4, July 1893, Pages 480–487, https://doi.org/10.2307/1882286 Published: 01 July 1893